2020
DOI: 10.1007/s00264-020-04713-8
|View full text |Cite
|
Sign up to set email alerts
|

Economic implications of decreased elective orthopaedic and musculoskeletal surgery volume during the coronavirus disease 2019 pandemic

Abstract: Purpose In order to reduce viral spread, elective surgery was cancelled in most US hospitals for an extended period during the COVID-19 pandemic. The purpose of this study was to estimate national hospital reimbursement and net income losses due to elective orthopaedic surgery cancellation during the COVID-19 pandemic. Methods The National Inpatient Sample (NIS) and the Nationwide Ambulatory Surgery Sample (NASS) were used to identify all elective orthopaedic and musculoskeletal (MSK) surgery performed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…In the research of the impacts on finance Goodell, 2020;Haroon & Rizvi, 2020;Phan & Narayan, 2020), researchers usually took the topics on stock, currency, financial system, gold and real estate trusts, insurance, and cryptocurrency, etc., in which the focus on stock market is the most, as stock is one of the most active financial indicators (Phan & Narayan, 2020). For the research about medical and health, many researchers discussed the economic challenges of COVID-19 on different medical departments, such as elective surgery (Best et al, 2020), dental surgery (Chamorro-Petronacci et al, 2020;Patel, 2020), etc. For human resources part, researchers' attention mainly focused on the employment situations and the general impacts and fluctuations in labor market (Kaur et al, 2020;Modrego et al, 2020;Webb et al, 2020).…”
Section: The Analyses Of the Pandemic's Economic Impacts On Differentmentioning
confidence: 99%
“…In the research of the impacts on finance Goodell, 2020;Haroon & Rizvi, 2020;Phan & Narayan, 2020), researchers usually took the topics on stock, currency, financial system, gold and real estate trusts, insurance, and cryptocurrency, etc., in which the focus on stock market is the most, as stock is one of the most active financial indicators (Phan & Narayan, 2020). For the research about medical and health, many researchers discussed the economic challenges of COVID-19 on different medical departments, such as elective surgery (Best et al, 2020), dental surgery (Chamorro-Petronacci et al, 2020;Patel, 2020), etc. For human resources part, researchers' attention mainly focused on the employment situations and the general impacts and fluctuations in labor market (Kaur et al, 2020;Modrego et al, 2020;Webb et al, 2020).…”
Section: The Analyses Of the Pandemic's Economic Impacts On Differentmentioning
confidence: 99%
“…Bedard et al [ 18 ] also found a profound impact of COVID-19 on their arthroplasty volumes in the USA. Best et al [ 19 ], in a national surgical survey, identified that all the elective orthopaedics were significantly reduced throughout the USA. This resulted in a severe loss in the incomes of the orthopaedic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to the best of our knowledge, this is the first study to clarify the impact of COVID-19 on surgical treatments from 2019 to 2020. Some medical institutes are facing difficulty surviving owing to the decreased revenue [ 14 , 15 ]. According to our output, hospital beds may be unused during this phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%